R+6=-14

Simple and best practice solution for R+6=-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for R+6=-14 equation:


Simplifying
R + 6 = -14

Reorder the terms:
6 + R = -14

Solving
6 + R = -14

Solving for variable 'R'.

Move all terms containing R to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + R = -14 + -6

Combine like terms: 6 + -6 = 0
0 + R = -14 + -6
R = -14 + -6

Combine like terms: -14 + -6 = -20
R = -20

Simplifying
R = -20

See similar equations:

| 5m+0.50=11.50 | | okx^3=343 | | m+0.50=11.50 | | -8+p=6p-6-3p | | 12x+8=8x+(-20) | | 6x-36=6 | | 5(2x-3)+4=4(2x+1)-7 | | 30=7.5x^2 | | 6(6-6p)=36+5p | | x^6-5x^4+4x^2+x+8=0 | | 2z=4z-2 | | -4(3+a)-6(1-a)=-8 | | -12=4(w-5)-6w | | -4(3+a)-6(1-a)=8 | | 32=28y+0 | | 12t^3-9t^2+28t=3t^2(4t-3)+7(4t-3) | | 13x+42=4x+5 | | 6y+1.5x=8 | | 2(x-3)+2=4(x+6)-30 | | -2+2p=-14 | | 13y+(4y)(3x)+x= | | 5x+15=15-3x+9 | | 4y-6=-22 | | 2(x-4)+3=4x+7 | | 6x^2+47x+92=0 | | (2x+28)=(3x+137) | | -24-7n=-8(3-6n) | | 42=3(2-3n)-6 | | -19=3(7+3n)+8(8n-5) | | 180=111-u | | -12+19/-7= | | -12+-42/-7= |

Equations solver categories